The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/fst.86621
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of pigmented and non-pigmented flakes glutinous rice (ampiang) on chemical compositions, free fatty acids compositions, amino acids compositions, dietary fiber content, and antioxidant properties

Abstract: The purpose of this study was to compare the characteristics of flakes rice made pigmented and non-pigmented glutinous rice grain on chemical composition, fatty acid, amino acid, dietary fiber, and antioxidant properties. Flakes glutinous rice (FGR) made glutinous rice grain that has been pre-roasted and then flattened. This product contains an endosperm and rice bran layer. So that, it is rich in nutrients and bioactive compounds that have antioxidant properties that are beneficial to health. The process of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
6
0
3
Order By: Relevance
“…Kadar air terendah terdapat pada flakes dari G48 dengan TK30:TD70. Hasil penelitian lain dari Amrinola et al (2022) menyatakan bahwa flakes yang dihasilkan berkisar antara 8,65-10,27% dan produk flakes glutinous rice dan flakes high protein soymeal sebesar 8,96% (Fasuan et al, 2021). Flakes tepung kedelai tergerminasi tidak jauh berbeda dengan kedua penelitian tersebut namun sedikit lebih rendah.…”
Section: Kadar Air Flakesunclassified
See 1 more Smart Citation
“…Kadar air terendah terdapat pada flakes dari G48 dengan TK30:TD70. Hasil penelitian lain dari Amrinola et al (2022) menyatakan bahwa flakes yang dihasilkan berkisar antara 8,65-10,27% dan produk flakes glutinous rice dan flakes high protein soymeal sebesar 8,96% (Fasuan et al, 2021). Flakes tepung kedelai tergerminasi tidak jauh berbeda dengan kedua penelitian tersebut namun sedikit lebih rendah.…”
Section: Kadar Air Flakesunclassified
“…Sampel dengan kadar protein terendah adalah perlakuan G24 dengan perbandingan TK70:TD30, sebesar 16.33%. Kadar protein ini lebih tinggi dibandingkan flakes yang dihasilkan oleh Amrinola et al (2022). Kadar protein flakes dari kedelai tergerminasi ini tidak berbeda jauh dengan kadar protein flakes yang dihasilkan oleh Fasuan et al (2021), yaitu sebesar 29,05%.…”
Section: Kadar Proteinunclassified
“…The temperature during PEF with moderate electric intensity and short duration pulses was 48.0 ± 0.6 °C, so the thermal degradation of the anthocyanin may have been less affected than with MAE. For the important reason of thermal degradation of the anthocyanin, the results of He et al (2017) and Figueiredo et al (1996) found that anthocyanins were evenly oxidized at temperatures higher than 50 °C, therefore it was appropriate to select 50 °C as the optimum process temperature. For the purpose of enhancing the anthocyanin extraction from black rice, it was necessary to consider both the mechanism of each technique and the extraction temperature.…”
Section: Effect Of Assisted-extraction Techniques On the Grain Surfac...mentioning
confidence: 99%
“…As a result of their lower toxicity compared to that of methanol and hydrochloric acid, ethanol and water acidified with acetic acid and organic acids were extensively used as solvents for anthocyanins and other bioactive chemicals extraction from black rice (Escribano-Bailón et al, 2004). In addition, water was considered as an optional new and environmentally friendly solvent for the extraction of bioactive compounds, as well as anthocyanins from black rice (He et al, 2017;Prommachart et al, 2020;Salee et al, 2022). Furthermore, extraction procedures that use water as a solvent were linked to an increase in environmental and health concerns (Carpentieri et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Ampiang in minangese describes as FGR [3]. In the process, FGR were flattened-pre-roasted rice [4]. One of the locations to relish amping dadiah is Bukittinggi.…”
Section: Introductionmentioning
confidence: 99%